THE DYNAMICS OF ARMS CONTROL AGREEMENTS IN THE POST-COLD WAR ERA (International Journal of Food and Nutritional Sciences, 2023)
The post-Cold War era has profoundly transformed the landscape of arms control agreements, shifting from a bipolar focus on U.S.-Russia relations to a more complex and multipolar global security environment. Initially marked by optimism for disarmament, this period witnessed significant reductions in nuclear arsenals through treaties like the Strategic Arms Reduction Treaty (START) and efforts to secure weapons of mass destruction (WMDs) in the former Soviet Union. However, the emergence of new nuclear states, such as India, Pakistan, and North Korea, as well as the challenges posed by non-state actors and technological advancements, has complicated traditional arms control frameworks. The proliferation of missile technology and the development of new military capabilities, including cyber and autonomous weapons, have further tested the existing agreements designed primarily for managing nuclear arsenals. The collapse of key treaties, such as the Intermediate-Range Nuclear Forces (INF) Treaty and the U.S. withdrawal from the Anti-Ballistic Missile (ABM) Treaty, signals a growing divergence in strategic interests and a waning commitment to arms control. Additionally, the rise of China as a significant military power has introduced new dimensions to arms control discussions, necessitating a broader, multilateral approach.